If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(3y + -6) + 4(5y + -8) = -18 Reorder the terms: -2(-6 + 3y) + 4(5y + -8) = -18 (-6 * -2 + 3y * -2) + 4(5y + -8) = -18 (12 + -6y) + 4(5y + -8) = -18 Reorder the terms: 12 + -6y + 4(-8 + 5y) = -18 12 + -6y + (-8 * 4 + 5y * 4) = -18 12 + -6y + (-32 + 20y) = -18 Reorder the terms: 12 + -32 + -6y + 20y = -18 Combine like terms: 12 + -32 = -20 -20 + -6y + 20y = -18 Combine like terms: -6y + 20y = 14y -20 + 14y = -18 Solving -20 + 14y = -18 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 14y = -18 + 20 Combine like terms: -20 + 20 = 0 0 + 14y = -18 + 20 14y = -18 + 20 Combine like terms: -18 + 20 = 2 14y = 2 Divide each side by '14'. y = 0.1428571429 Simplifying y = 0.1428571429
| 8-2x=24-8x | | 19x-7=7+12x | | 14-3t+t-5=-4-2 | | 2x+4=3y | | 4x-15=1+x | | 12x-40=24-8x | | 3y=2x+4 | | 5x-4(0)=60 | | x-8+8=-x | | 4x+3=7x-4x | | -4-5x=-21-3x | | 2.3w-11=-1.75w | | 2x^2-4y=24 | | 5(0)-4y=60 | | b-9+3b=24 | | 8p+12q= | | 2r-3+3=-r | | 5-4(2x-3)=13 | | 3x-23=7x+17 | | 8p-3(p-6)=-7 | | 4t+1=t+5+t-3 | | 3-6=9 | | 2b-5=4b+1 | | (1/2)*b+4=(1/8)*b+88 | | 2b-5=4b-1 | | -12r+3+r=-7-12 | | 70=-10(2+m) | | -3(r+2)=-53 | | R^2+11r+28=0 | | 673/4=x | | 5x-8(0)=80 | | 9(5x-7)+9=46 |